The Implementation LAZISMU Communication Strategy To Achieve The Reputation - Adzan Desar Deryansyah (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2021)
Lazismu performs its duties and functions to collect donations from Muzzaki for the benefit of Zakat, Infaq and Shadaqah It is not separated from communication activities, one of which is conducting communication strategy activities. Communication strategies are inseparable from the functions of the organization carrying out its series of activities. The importance of strategy is one of the supporting programs that have been determined. The purpose of this study is to find out Lazismu's communication strategy. The research method used in this study is descriptive qualitative method. From the findings of research and discussion can be known that socialization strategy using the media is an inevitability because it will directly present the institution to the middle of the community, the selection of media that has been done is appropriate because Lazismu chose to socialize through social media while the social media chosen is 3 media platforms that are very favored by the public, especially young people as their potential target for the achievement of Lazismu's goals and the achievement of ZIS targets in Indonesia.